2018
DOI: 10.1159/000491781
|View full text |Cite
|
Sign up to set email alerts
|

Breast Ultrasound during Lactation: Benign and Malignant Lesions

Abstract: Background: Structural changes during lactation make breast physical examination difficult. When breast problems occur, patients are often referred for an ultrasound (US) scan. Most breast lesions diagnosed in these patients are benign, but the diagnosis of breast cancer is a challenge. We aim to demonstrate the spectrum of US imaging findings in lactating women. Methods: 77 breastfeeding patients who underwent breast US in our department between February 2012 and March 2017 were evaluated. Patients' electroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
1
5
0
2
Order By: Relevance
“…Previous studies have demonstrated that ultrasound findings concerning for breast malignancy include taller-thanwide hypoechoic lesions with irregular shape, ill-defined or microlobulated margins, increased posterior acoustic enhancement, and cystic components. [24][25][26] These findings were also observed on ultrasound imaging in patients who had a breast cancer recurrence after NSM.…”
Section: Discussionsupporting
confidence: 59%
“…Previous studies have demonstrated that ultrasound findings concerning for breast malignancy include taller-thanwide hypoechoic lesions with irregular shape, ill-defined or microlobulated margins, increased posterior acoustic enhancement, and cystic components. [24][25][26] These findings were also observed on ultrasound imaging in patients who had a breast cancer recurrence after NSM.…”
Section: Discussionsupporting
confidence: 59%
“…Proper evaluation of a pregnant/lactating breast is thus crucial to ensure timely diagnosis of lumps that may require prompt management. However, evaluation of a lactating breast is challenging, both clinically and radiologically,1 4 due to the structural changes described earlier. Masses could also be obscured during radiographic evaluation, leading to a delay in diagnosis 5…”
Section: Discussionmentioning
confidence: 99%
“…7) and diffuse hypervascularity is noted both in pregnancy and lactation. 24,25,27 Lactation changes on MRI result in increased background enhancement, likely because of increased vascularity, and diffusely increased T2 signal, likely secondary to the aqueous makeup of breast milk (Fig. 8).…”
Section: Breast Lactationmentioning
confidence: 99%
“…Dilated ducts will be apparent during lactation, (Fig. 7) and diffuse hypervascularity is noted both in pregnancy and lactation 24,25,27 …”
Section: Breastmentioning
confidence: 99%